2011
DOI: 10.1073/pnas.1010334108
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of the ubiquitin ligase Nedd4L in lung epithelia causes cystic fibrosis-like disease

Abstract: Cystic fibrosis is caused by impaired ion transport due to mutated cystic fibrosis transmembrane conductance regulator, accompanied by elevated activity of the amiloride-sensitive epithelial Na + channel (ENaC). Here we show that knockout of the ubiquitin ligase Nedd4L (Nedd4-2) specifically in lung epithelia (surfactant protein C-expressing type II and Clara cells) causes cystic fibrosis-like lung disease, with airway mucus obstruction, goblet cell hyperplasia, massive inflammation, fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
109
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(117 citation statements)
references
References 40 publications
7
109
1
Order By: Relevance
“…Recently it was shown that ITCH knock-out mice also showed age-dependent alterations in spermatogenesis (38). NEDD4L knock-out mice died perinatally due to disrupted lung function (21,22). Therefore, it remains to clarify whether NEDD4 family ubiquitin ligases play a unique or redundant role in regulating stability of Dvl family proteins and FIGURE 6.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently it was shown that ITCH knock-out mice also showed age-dependent alterations in spermatogenesis (38). NEDD4L knock-out mice died perinatally due to disrupted lung function (21,22). Therefore, it remains to clarify whether NEDD4 family ubiquitin ligases play a unique or redundant role in regulating stability of Dvl family proteins and FIGURE 6.…”
Section: Discussionmentioning
confidence: 99%
“…By far, several proteins have been described as the substrates of NEDD4L, including ion and neurotransmitter channels, growth factor receptors, signaling intermediates, and tight junction molecules (17)(18)(19)(20). NEDD4L knock-out mice die perinatally due to impaired lung function (21,22).…”
mentioning
confidence: 99%
“…We first used the Scnn1a-Cre allele identified in our driver screen that targeted AT1 cells in the flattening stage and were thus committed to terminal differentiation. Although SCNN1A was detected in other cell types than AT1 (Borok et al, 2006;Johnson et al, 2002Johnson et al, , 2006Kimura et al, 2011), the Scnn1a-Cre allele was active in AT1 cells after E19, consistent with the perinatal upregulation of Scnn1a in the distal lung epithelium (Fig. S7D) (Chang et al, 2013), and reached a targeting efficiency (defined as the percentage of AT1 cells that were targeted) of 71% (n=153 cells) and specificity (defined as the percentage of targeted cells that were AT1 cells) of 95% (n=176 cells from three mice) (Fig.…”
Section: Developing At1 Cells Retain Cellular Plasticitymentioning
confidence: 99%
“…The in vivo relevance of Nedd4-2 has been recently highlighted. Nedd4-2 knock-out mice die perinatally because of a failure to inflate the lungs (44,45), Nedd4-2 shows a protective regulatory role against the development of cystic fibrosis in lung (45), and it has been directly implicated in the development of peripheral neuropathic pain (46). The role of TrkA on pain has been well established for a long time in mice (47) and humans (48).…”
Section: Discussionmentioning
confidence: 99%